1998
DOI: 10.1093/gerona/53a.1.m47
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Physical Restraint Removal and Falls and Injuries Among Nursing Home Residents

Abstract: Physical restraint removal does not lead to increases in falls or subsequent fall-related injury in older nursing home residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 0 publications
1
89
0
4
Order By: Relevance
“…(35) This is further supported in a later study where Capezuti et al found that the removal of restraints did not increase fall risk or subsequent injuries from falls in nursing home residents. (36) In our study, we found that the use of restraints in our hospital for agitated or disruptive patients was not common. This may be due to better awareness about the consequences of restraint use in the frail elderly population.…”
Section: Na: Not Availablementioning
confidence: 57%
“…(35) This is further supported in a later study where Capezuti et al found that the removal of restraints did not increase fall risk or subsequent injuries from falls in nursing home residents. (36) In our study, we found that the use of restraints in our hospital for agitated or disruptive patients was not common. This may be due to better awareness about the consequences of restraint use in the frail elderly population.…”
Section: Na: Not Availablementioning
confidence: 57%
“…muscle weakness, balance impairment, environmental hazards, restraints). The use of physical restraints, in particular, has been extensively debated, (Capezuti, Strumpf, Evans, Grisso, & Maislin, 1998;Hamers & Huizing, 2005), but data on their effect on falls is still inconclusive, and only few studies were available for each restraint device (i.e. bedrails, trunk restraints).…”
Section: Discussionmentioning
confidence: 99%
“…The most common indication for use of PR was high risk of falls. The validity of this indication is questioned by studies showing a lower fall or injury incidence during restraint reduction in nursing homes (12,13). The difference in the use of PR for more than 24 hours between hospitals and nursing homes, although not justified by it, can probably be explained by the higher number of acutely ill cognitively impaired patients in geriatric hospital wards.…”
Section: To the Editormentioning
confidence: 99%